A reinforced composite structure for the interface of foamed concrete and oil and gas pipelines and a method of manufacture
Patent Information
- Application Number
- CN202611305180.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-11-03
AI Technical Summary
The existing 3LPE anti-corrosion layer of oil and gas pipelines has insufficient interfacial adhesion between the anti-corrosion layer and foamed concrete, which makes it difficult for the foamed concrete to effectively restrain the deformation of the pipeline caused by temperature and pressure, resulting in low interfacial load transfer efficiency and poor overall integrity.
By plasma activation treatment of the outer surface of 3LPE steel pipe to form a plasma-activated interface layer, an interface adhesive is sprayed on it, then reinforcing material is wrapped around it, and finally modified fiber-reinforced foam concrete is poured to form an enhanced composite structure.
It significantly improves the interfacial shear bond strength between foamed concrete and 3LPE steel pipe, effectively constrains the temperature and vibration deformation of the pipeline during long-term operation, and ensures the safe operation of long-distance oil and gas pipelines.
Smart Images

Figure CN123025564A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of oil and gas pipeline transportation, and mainly to an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines and its preparation method. Background Technology
[0002] Oil and gas pipelines, as a crucial component of my country's modern energy network, play an irreplaceable role in ensuring national energy security. According to the "China Natural Gas Development Report (2025)" released by the National Energy Administration, by the end of 2024, the total length of long-distance natural gas pipelines nationwide had exceeded 128,000 kilometers. Because oil and gas pipelines often face harsh environments such as high temperatures and high pressures during operation, extremely high requirements are placed on their safety, thermal stability, and durability. Therefore, oil and gas pipelines generally use specially made steel pipes with a three-layer 3LPE anti-corrosion coating. After installation, oil and gas pipelines typically require full-coverage filling protection. Foamed concrete, as a filling material with excellent fluidity and moderate strength, has been increasingly widely used in the filling protection of oil and gas pipeline tunnels in recent years.
[0003] The filling and protection design of foamed concrete mainly utilizes the interfacial shear bond force between foamed concrete and pipelines to constrain deformation caused by factors such as thermal expansion and contraction, pressure fluctuations, and mechanical vibrations during the operation of long-distance pipelines. This prevents excessive deformation from causing safety accidents such as support deformation, seal failure, or even system damage. However, the outer polyethylene layer of the 3LPE anti-corrosion coating for oil and gas pipelines is a non-polar crystalline material with excellent chemical inertness, surface smoothness (cleanliness Sa2.5 grade, surface roughness less than 50µm), and low surface energy (less than 31mN·m). -1 Due to its characteristics, the interface between foamed concrete and steel pipes is prone to forming a weak bonding layer, leading to low load transfer efficiency, poor overall integrity, and even shear slip. Traditional methods of improvement, such as welding studs to the inner wall of the steel pipe, creating holes, or sandblasting, can damage the integrity of the 3LPE anti-corrosion layer, increasing the risk of pipeline corrosion. Therefore, there is an urgent need for a method to significantly improve the interfacial adhesion between foamed concrete and steel pipes without compromising the function of the 3LPE anti-corrosion layer, in order to fully ensure the safe operation of long-distance oil and gas pipelines.
[0004] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this application is to provide an enhanced composite structure and preparation method for the interface between foamed concrete and oil and gas pipelines, which aims to solve the problem that the insufficient interfacial bonding between the 3LPE anti-corrosion layer and foamed concrete in existing oil and gas pipelines makes it difficult for the foamed concrete filler to effectively restrain the deformation of oil and gas pipelines caused by temperature and pressure during operation.
[0006] The technical solution of this application is as follows: A method for preparing an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, comprising the following steps: (1) Plasma activation treatment is performed on the outer surface of the 3LPE steel pipe to form a plasma activation interface layer; (2) A uniformly sprayed interface adhesive is applied to the surface of the plasma-activated interface layer to form an interface adhesive layer; (3) Wrap a reinforcing material around the surface of the interface adhesive layer; (4) Pour modified fiber-reinforced foamed concrete.
[0007] The method for preparing the enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein in step (1), the working gas is one or more of oxygen, nitrogen, and inert gas; the inert gas is helium or argon. The plasma radio frequency power is 150~400W, and the activation time is 20~90s.
[0008] The method for preparing the enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein in step (1), the working gas is a combination of oxygen and inert gas, and the volume ratio of oxygen to inert gas is 1:1 to 3:1; The plasma activation treatment is performed using a radio frequency capacitively coupled plasma device or an inductively coupled plasma device.
[0009] The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein the thickness of the interface adhesive layer is 0.2~0.5mm; The interface adhesive, by weight, is composed of the following raw materials: 80-100 parts of resin base material, 5-12 parts of reactive silane, 20-50 parts of aqueous alcohol solution, and 0.5-2 parts of thixotropic agent; The resin substrate is one or more of epoxy resin, polyurethane, phenolic resin, urea-formaldehyde resin, and polyacrylic acid resin. The reactive silane is one or more of aminosilane, epoxysilane, methacryloxysilane, vinylsilane, and isocyanate silane; The aqueous alcohol solution is composed of a homogeneous mixture of alcohol and water, wherein the mass ratio of water to alcohol is 9:1 to 7:3; and the alcohol is one of ethanol, methanol, or isopropanol. The thixotropic agent is fumed silica or organobentonite.
[0010] The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein the method for preparing the interface binder includes the following steps: The aqueous alcohol solution is mixed with the resin substrate to obtain a resin solution; The reactive silane is added to the resin solution and hydrolyzed by stirring at 25~55°C; Add the thixotropic agent and stir until homogeneous to obtain the interfacial binder; During the stirring hydrolysis process, the stirring speed is 150~300 rpm, the stirring time is 5~10 min, and the hydrolysis time is 40~200 min.
[0011] The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein, in step (3), the reinforcing material is a three-dimensional mesh reinforcing material with a serrated surface; The reinforcing material is joined longitudinally and circumferentially using a binding and overlapping method.
[0012] The method for preparing an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein the serration height of the three-dimensional mesh reinforcement material with serrated features is 0.03 to 0.08 times the diameter of the steel pipe, the serration angle is 45° to 75°, and the ratio of the bottom spacing of the serrations to the serration height is (4 to 8): 1. The three-dimensional mesh reinforcement material with serrated features is galvanized steel wire mesh, steel-plastic geogrid, or alkali-resistant glass fiber mesh; The longitudinal and circumferential overlaps have an overlap length of 0.2~0.4D along the circumferential direction and an overlap length of 0.5~0.8D along the longitudinal direction.
[0013] The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein in step (4), the thickness of the modified fiber-reinforced foamed concrete covering the surface of the 3LPE steel pipe is not less than 30cm. In step (4), the modified fiber-reinforced foamed concrete comprises, by weight, the following raw materials: 60-80 parts cement, 30-50 parts nano-reinforcing agent, 5-8 parts modified fiber, 0.5-3 parts foaming agent, and 50-80 parts first water; The cement is ordinary Portland cement with a strength grade of 425; The nano-reinforcing agent is one or more of nano-calcium carbonate, nano-silica, and nano-CSH particles. The foaming agent is one or more of the following: plant protein foaming agents, animal protein foaming agents, anionic foaming agents, cationic foaming agents, and amphoteric foaming agents. The modified fiber is obtained by grafting polar monomers onto the fiber surface for activation. The polar monomer is one or more of acrylic acid, methacrylic acid, acrylamide, glycidyl methacrylate, and maleic anhydride. The fiber is one or more of the following: polypropylene fiber, polyvinyl alcohol fiber, polyester fiber, glass fiber, and basalt fiber. The wet density of the modified fiber-reinforced foamed concrete is 800~1200 kg / m³. 3 .
[0014] The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein the method for preparing the modified fiber includes the following steps: The polar monomer was prepared into a modified solution with a concentration of 0.1–2.0 mol / L; The fiber is immersed in the modified solution and vacuum impregnated; The polar monomers are subjected to ultraviolet irradiation to cause free radical graft polymerization on the fiber surface; (4) Wash with deionized water and vacuum dry to constant weight to obtain the modified fiber; The vacuum impregnation process is performed by vacuum impregnation at 25℃~40℃ for 2~4 hours; The ultraviolet irradiation process involves irradiating for 20 to 40 minutes under an ultraviolet lamp with a power of 500 to 1000W, at a distance of 10 to 20 cm. The vacuum drying process is carried out at 60~80℃; The preparation method of the modified fiber-reinforced foamed concrete includes the following steps: The cement, the nano-reinforcing agent, and the modified fiber are mixed evenly to obtain a first mixture; Add the first water to the first mixture and mix evenly to obtain the second mixture; The foaming agent is diluted with a second water at a dilution ratio of 50 to 80 times by mass, and then foamed to produce a product with a density of 30 to 50 kg / m³. 3 foam; The foam is added to the second mixture and mixed to obtain the modified fiber-reinforced foam concrete.
[0015] A reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, wherein the structure is prepared by the method described above for preparing a reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, and the structure includes: Steel pipe body; A 3LPE anti-corrosion coating is applied to the outer wall of the steel pipe body; The plasma-activated interface layer is the region formed on the outer surface of the 3LPE anti-corrosion coating by plasma activation treatment. An interface adhesive layer is disposed on the plasma-activated interface layer; The reinforcing material layer is longitudinally and circumferentially overlapped on the interface adhesive layer using a binding and overlapping method; A modified fiber-reinforced foamed concrete layer is disposed on the reinforcing material layer.
[0016] Beneficial effects: The reinforced composite structure for the interface between foamed concrete and oil and gas pipelines in this application can significantly improve the shear bond strength between foamed concrete and 3LPE steel pipe, effectively constraining the temperature deformation and vibration deformation generated during long-term operation of the pipeline, which is of great value for ensuring the long-term safe operation of long-distance oil and gas pipelines. Attached Figure Description
[0017] Figure 1 This is a cross-sectional schematic diagram of the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to this application.
[0018] Figure 2 This is a schematic diagram of the interface shearing test of Embodiment 1 and Comparative Example 1 of this application.
[0019] Labeling Explanation: 10, Steel pipe body; 20, Interface adhesive layer; 30, Reinforcing material layer; 40, Modified fiber-reinforced foamed concrete layer; 100, Specimen; 101, 3LPE steel pipe without foamed concrete wrapping; 201, Pressure platform; 202, Steel pressure support; 203, Upper pressure plate; 204, Sensor; 205, Arrow. Detailed Implementation
[0020] This application provides an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, and a method for its preparation. To make the objectives, technical solutions, and effects of this application clearer and more explicit, the following provides a more detailed description. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0021] This application provides a method for preparing an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, comprising the following steps: (1) Plasma activation treatment is performed on the outer surface of 3LPE steel pipe to form a plasma activation interface layer.
[0022] In this application, a steel pipe with a 3LPE anti-corrosion coating (hereinafter referred to as 3LPE steel pipe) is used as the object, and the outer surface of the 3LPE steel pipe is first subjected to plasma activation treatment.
[0023] Plasma activation treatment can be performed using a radio frequency capacitively coupled plasma (CCP) device or an inductively coupled plasma (ICP) device. During plasma activation treatment, the working gas can be one or a mixture of two or more of oxygen, nitrogen, helium, and argon; in this application, a combination of oxygen and an inert gas is used, wherein the volume ratio of oxygen to inert gas is 1:1 to 3:1; the plasma radio frequency power can be 150 to 400 W, and the activation time can be 20 to 90 s.
[0024] By using the above parameters to perform plasma activation treatment on 3LPE steel pipes, the surface free energy and hydrophilicity of the 3LPE steel pipes can be significantly improved while maintaining the surface integrity, thus achieving a complete transformation of the steel pipe surface from "non-polar inert" to "polar reactive".
[0025] (2) A uniformly sprayed interface adhesive is applied to the surface of the plasma-activated interface layer to form an interface adhesive layer.
[0026] In this step, the thickness of the interface adhesive layer can be 0.2~0.5mm. After the interface adhesive is applied, the reinforcing material can be directly wrapped around it.
[0027] Furthermore, the interface adhesive is composed of a resin base material, a reactive silane, an aqueous alcohol solution, and a thixotropic agent. Specifically, the interface adhesive, by weight, is composed of the following raw materials: 80-100 parts of resin base material, 5-12 parts of reactive silane, 20-50 parts of aqueous alcohol solution, and 0.5-2 parts of thixotropic agent.
[0028] The resin substrate can be one or more of epoxy resin, polyurethane, phenolic resin, urea-formaldehyde resin, and polyacrylic acid resin.
[0029] The reactive silane is one or more of aminosilane, epoxysilane, methacryloxysilane, vinylsilane, and isocyanate silane.
[0030] Aqueous alcohol solutions are composed of a homogeneous mixture of alcohol and water, wherein the mass ratio of water to alcohol is 9:1 to 7:3. The alcohol is one of ethanol, methanol, or isopropanol.
[0031] Thixotropic agents, such as fumed silica or organobentonite, are used to prevent spray sagging and ensure uniformity of adhesive thickness.
[0032] Furthermore, the preparation method of the above-mentioned interfacial adhesive includes the following steps: (1) The resin substrate is mixed and diluted with an alcoholic solution to obtain a resin solution; (2) Add reactive silane to the resin solution and stir and hydrolyze at 25~55℃. The stirring speed is 150~300rpm, the stirring time is 5~10min, and the hydrolysis time is 40~200min. (3) Add thixotropic agent to the fully hydrolyzed mixed solution, mix and stir for 3-5 minutes until uniform, and obtain interface binder.
[0033] The reactive groups (such as amino and epoxy groups) contained in the interface adhesive of this application will chemically bond with the surface of the activated 3LPE steel pipe, and the silanoxy group at the other end will form a chemical connection with the inorganic hydration products in the foamed concrete, thereby realizing the "two-way molecular bridging" effect between the polyethylene surface and the inorganic material.
[0034] (3) Wrap reinforcing material on the surface of the interface adhesive layer.
[0035] In this step, the reinforcing material is a three-dimensional mesh reinforcing material with a serrated surface.
[0036] Preferably, the three-dimensional mesh reinforcement material with serrated features can be galvanized steel wire mesh, steel-plastic geogrid, or alkali-resistant glass fiber mesh.
[0037] Preferably, the serration height of the three-dimensional mesh reinforcement material with serrated features is 0.03~0.08 times the diameter of the steel pipe, the serration angle is 45°~75°, and the ratio of serration spacing to serration height is (4~8):1. Here, serration height refers to the vertical distance from the tooth tip to the tooth root (valve bottom). Serration angle refers to the angle between the serration slope and the horizontal reference plane. Serration spacing refers to the distance between the centers of the tips of two adjacent serrations.
[0038] The 3D mesh reinforcement material with the aforementioned serrated features significantly increases the actual contact area between the 3LPE steel pipe and the foamed concrete, and increases the geometric roughness of the interface. After the foamed concrete is poured and hardened, the serrated protrusions embed into the interior of the foamed concrete, forming a mechanical interlocking structure similar to mortise and tenon joints, which greatly increases the mechanical interlocking force at the interface. Simultaneously, the embedding effect of the reinforcement material creates a stronger local bearing zone at the root of the serrations in the foamed concrete, improving the overall shear bearing capacity of the interface. Furthermore, the high tensile strength of the 3D serrated reinforcement material itself can improve the elastic shear stiffness of the interface, bearing the shear force at the interface. When shear slip occurs at the interface, it can effectively resist relative displacement deformation and provide residual shear capacity at the interface in the ultimate state, avoiding brittle shear failure of the interface.
[0039] Furthermore, the reinforcing material is joined using a binding lap splice method in both the longitudinal and circumferential directions. The circumferential lap length is 0.2~0.4D (D is the diameter of the steel pipe), and the longitudinal lap length is 0.5~0.8D. The longitudinal and circumferential lap splices ensure the integrity and stress continuity of the reinforcing material in three-dimensional space. The double laps in both directions form a continuous "sleeve" structure, making the reinforcing field around the pipe uniform, preventing abrupt stress transfer, and avoiding shear slip failure at the lap ends. The circumferential lap length refers to the length of overlap between the two ends of the reinforcing material after it wraps around the steel pipe once. The longitudinal lap length refers to the length of overlap between the ends of two adjacent reinforcing material sections along the length of the steel pipe.
[0040] (4) Pour modified fiber-reinforced foamed concrete.
[0041] In this step, modified fiber-reinforced foamed concrete is poured around the 3LPE steel pipe, which is wrapped with reinforcing material, until the 3LPE steel pipe is completely covered and protected by the modified fiber-reinforced foamed concrete. After pouring, the foamed concrete is covered with a film for moisture curing until the specified age (generally 28 days). The thickness of the modified fiber-reinforced foamed concrete covering the 3LPE steel pipe is not less than 30cm.
[0042] Furthermore, the raw materials for modified fiber-reinforced foamed concrete include cement, nano-reinforcing agents, modified fibers, foam, and water. Specifically, modified fiber-reinforced foamed concrete, by weight, comprises the following raw materials: 60-80 parts cement, 30-50 parts nano-reinforcing agent, 5-8 parts modified fiber, 0.5-3 parts foaming agent, and 50-80 parts first water.
[0043] The cement is ordinary Portland cement with a strength grade of 425.
[0044] The nano-reinforcing agent is one or more of nano-calcium carbonate, nano-silica, and nano-CSH particles.
[0045] The foaming agent is one or more of the following: plant protein foaming agents, animal protein foaming agents, anionic foaming agents, cationic foaming agents, and amphoteric foaming agents.
[0046] Furthermore, the modified fiber is obtained by graft polymerization activation of polar monomers. Specifically, the preparation method of the modified fiber includes the following steps: (1) Preparation of modified solution: Prepare a modified solution with a concentration of 0.1 to 2.0 mol / L by preparing the polymerizable polar monomer.
[0047] The polar monomer is one or more of acrylic acid (AA), methacrylic acid (MAA), acrylamide (AM), glycidyl methacrylate (GMA), and maleic anhydride (MAH).
[0048] (2) Immerse the fiber in the modified solution and vacuum impregnate it at 25℃~40℃ for 2~4h to allow the polar monomer to fully penetrate into the micropores on the surface of the fiber.
[0049] The fiber is one or more of the following: polypropylene fiber, polyvinyl alcohol fiber, polyester fiber, glass fiber, and basalt fiber.
[0050] (3) Irrigate the impregnated fiber under a UV lamp with a power of 500~1000W for 20~40min at a distance of 10~20cm to allow the polar monomer to undergo free radical grafting polymerization on the fiber surface.
[0051] (4) Wash with deionized water 3 to 5 times, and vacuum dry at 60 to 80°C to constant weight to obtain modified fiber with surface activated by grafted polar monomer.
[0052] Using this specific modified fiber, the interfacial bonding force between foamed concrete and pipeline can be significantly improved through three mechanisms: chemical bonding, mechanical interlocking and stress bridging. Specifically: (1) The carboxyl, amide and anhydride groups contained in the polar monomers grafted on the fiber surface can react with the hydration products of foamed concrete to generate covalent bonds and form a dense three-dimensional network structure, which significantly improves the interfacial bonding force between the fiber and the cement matrix, thereby improving the integrity and crack resistance of foamed concrete and reducing the interface debonding caused by shrinkage cracking of the cement matrix; (2) The fiber chain segments near the interface connect the foamed concrete matrix and the interface adhesive layer respectively. The presence of the fiber makes an "anchoring layer" form near the surface of the pipeline, which enhances the physical interlocking effect between the interfaces; (3) Through the bridging effect of the modified fiber in the foamed concrete and at the foamed concrete-pipe interface, the stress at the foamed concrete-pipe interface can be transferred to the interior of the foamed concrete through strong interfacial bonding, realizing the continuity of stress transmission in the path of foamed concrete-fiber-interface layer-pipe, and avoiding stress concentration at the interface that leads to shear failure at the weak part of the interface.
[0053] Furthermore, the wet density of the modified fiber-reinforced foamed concrete is 800~1200 kg / m³. 3 The 28-day unconfined compressive strength is 3~10MPa. When the wet density of foamed concrete is too high, the high density and particle content of the slurry lead to high resistance and segregation during pipeline pumping. When the wet density of foamed concrete is too low, the foam volume ratio in the foamed concrete slurry reaches more than 50%, and foam aggregation and collapse are inevitable during long-distance pipeline pumping, affecting the uniformity of the slurry after hardening. In addition, the adhesion between low wet density foamed concrete and 3LPE steel pipe is also weak after hardening, which is not conducive to the protection of oil and gas pipelines.
[0054] Furthermore, the preparation method of modified fiber-reinforced foamed concrete includes the following steps: (1) Weigh the powder (cement, nano-reinforcing agent) and modified fiber by weight into a mixer and mix them evenly to obtain the first mixture.
[0055] (2) Add the weighed first water to the first mixture while stirring. After mixing evenly, the second mixture is obtained.
[0056] (3) Dilute the foaming agent with second water at a dilution ratio of 50 to 80 times (by mass), that is, the mass ratio of foaming agent to second water is 1:50 to 80. The diluted foaming agent solution is then foamed using a physical foaming device to generate a density of 30 to 50 kg / m³. 3The uniform and dense foam is formed; wherein the second water in this step is not included in the above-mentioned amount of "50 to 80 parts of water". The specific amount of "0.5 to 3 parts of foaming agent" is diluted with additional water and foam is generated by foaming equipment, and then mixed with the second mixture.
[0057] (4) Add the prepared foam to the second mixture according to the preset volume (the preset volume is determined according to the wet density of the modified fiber reinforced foam concrete) and mix at low speed for 3~5 minutes to obtain the modified fiber reinforced foam concrete.
[0058] The wet density of modified fiber-reinforced foamed concrete is 800~1200 kg / m³. 3 The unconfined compressive strength at 28 days is 3~10 MPa.
[0059] Furthermore, this application also provides a reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, prepared using the above-described method for preparing a reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, and its structure is as follows. Figure 1 As shown, it includes: 10 steel pipe body; A 3LPE anti-corrosion coating is applied to the outer wall of the steel pipe body; The plasma-activated interface layer is the area formed on the outer surface of the 3LPE anti-corrosion coating by plasma activation treatment. An interface adhesive layer 20 is disposed on the plasma-activated interface layer; The reinforcing material layer 30 is longitudinally and circumferentially overlapped on the interface adhesive layer 20 by a binding and overlapping method; A modified fiber-reinforced foamed concrete layer 40 is disposed on the reinforcing material layer 30.
[0060] This application discloses a reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, comprising a 3LPE steel pipe, a plasma-activated interface layer, an interface adhesive layer, a reinforcing material layer, and a modified fiber-reinforced foamed concrete layer. Plasma activation treatment of the 3LPE anti-corrosion steel pipe surface creates a plasma-activated interface layer that effectively enhances the surface free energy and hydrophilicity without compromising the integrity of the anti-corrosion layer, thereby strengthening its chemical bonding with the interface adhesive. The reactive groups in the interface adhesive layer can form covalent bonds with the -OH and -COOH groups on the surface of the plasma-activated 3LPE steel pipe, and can also undergo condensation reactions with the hydration products in the modified fiber-reinforced foamed concrete to generate a stable inorganic silica gel network, achieving a "two-way molecular bridging" effect between the plasma-activated interface layer and the modified fiber-reinforced foamed concrete.
[0061] The present application will be further described below through specific embodiments.
[0062] Example 1 This embodiment provides a method for preparing an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, including the following steps: (1) Plasma activation treatment is applied to the outer surface of the 3LPE steel pipe to form a plasma-activated interface layer: Plasma activation treatment can be carried out using a radio frequency capacitively coupled plasma (CCP) device. The working gas is a combination of oxygen and argon, with a volume ratio of oxygen to argon of 2:1. The plasma radio frequency power is 250W, and the activation time is 60s.
[0063] (2) A uniformly sprayed interface adhesive is applied to the surface of the plasma-activated interface layer to form an interface adhesive layer.
[0064] First, prepare the interfacial binder.
[0065] The interface adhesive, by weight, is composed of the following raw materials: 90 parts resin base material, 8 parts reactive silane, 40 parts aqueous alcohol solution, and 1.5 parts thixotropic agent.
[0066] The resin substrate is bisphenol A type epoxy resin with an epoxy value of 0.52 mol / 100g.
[0067] The reactive silane used is γ-isocyanate-propyltriethoxysilane with a molecular weight of 247.
[0068] The aqueous alcohol solution is composed of a homogeneous mixture of alcohol and water, wherein the mass ratio of water to alcohol is 8:1. The alcohol is ethanol.
[0069] The thixotropic agent is fumed silica.
[0070] The preparation process includes the following steps: (a) The resin substrate is mixed and diluted with an aqueous alcohol solution to obtain a resin solution; (b) Add reactive silane to the resin solution and stir and hydrolyze at 35°C. The stirring speed is 200 rpm and the stirring time is 8 min. The hydrolysis time is 100 min. (c) Add the thixotropic agent to the fully hydrolyzed mixed solution, mix and stir for 4 minutes until uniform, and obtain the interface binder.
[0071] Finally, an interface adhesive is sprayed on, with a thickness of 0.3 mm.
[0072] (3) Wrap reinforcing material on the surface of the interface adhesive layer.
[0073] The reinforcing material is a three-dimensional mesh with a serrated feature, which is galvanized steel wire mesh. The serration height of the three-dimensional mesh reinforcing material with a serrated feature is 0.05 times the diameter of the steel pipe, the serration angle is 55°, and the ratio of the spacing between the bottom of the serrations to the serration height is 6:1.
[0074] The reinforcing material is joined by lap splicing in both the longitudinal and circumferential directions. The lap length in the circumferential direction is 0.3D (D is the diameter of the steel pipe), and the lap length in the longitudinal direction is 0.6D.
[0075] (4) Pour modified fiber-reinforced foamed concrete.
[0076] First, the modified fibers are prepared, including the following steps: (a) Preparation of the modified solution: Prepare a modified solution with a concentration of 1 mol / L by preparing polymerizable polar monomer acrylic acid (AA).
[0077] (b) Immerse the fiber in the modified solution and vacuum impregnate it at 35°C for 3 hours to allow the polar monomer to fully penetrate into the surface micropores of the polypropylene fiber.
[0078] (c) Irradiate the impregnated polypropylene fibers under an 800W UV lamp for 30 minutes at a distance of 15cm to allow the polar monomers to undergo free radical grafting polymerization on the surface of the polypropylene fibers.
[0079] (d) Wash with deionized water 4 times and vacuum dry at 70°C to constant weight to obtain modified fibers with surface activated by grafting polar monomers.
[0080] Then, modified fiber-reinforced foamed concrete was prepared.
[0081] Modified fiber-reinforced foamed concrete, by weight, is composed of the following raw materials: 70 parts cement, 40 parts nano-reinforcing agent, 7 parts modified fiber, 2 parts foaming agent, and 70 parts first water.
[0082] The cement is ordinary Portland cement with a strength grade of 425.
[0083] The nano-reinforcing agent is nano-calcium carbonate.
[0084] The foaming agent is sodium dodecylbenzenesulfonate, an anionic foaming agent.
[0085] A method for preparing modified fiber-reinforced foamed concrete includes the following steps: (a) Weigh out cement, nano-reinforcing agent and modified fiber by weight and put them into a mixer and mix them evenly to obtain the first mixture; (b) The weighed first water is added to the first mixture while stirring. After mixing evenly, the second mixture is obtained. (c) Dilute the foaming agent with water at a dilution ratio of 70 times (by mass). The diluted foaming agent solution is then foamed using a physical foaming device to produce a density of 40 kg / m³. 3 Uniform and dense foam; (d) Add the prepared foam to the second mixture according to the preset volume and mix at low speed for 4 minutes to obtain modified fiber-reinforced foam concrete with a wet density of 1000 kg / m³. 3 .
[0086] Finally, modified fiber-reinforced foamed concrete was poured around the 3LPE steel pipe, which was covered with reinforcing material, until the 3LPE steel pipe was completely covered and protected by the modified fiber-reinforced foamed concrete, resulting in a specimen, which is the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines of this application. The specimen was then cured under standard curing conditions of 20±5℃ and humidity ≥90%.
[0087] Comparative Example 1: It is basically the same as Example 1, except that Comparative Example 1 did not undergo plasma activation treatment.
[0088] Comparative Example 2: It is basically the same as Example 1, except that no interface adhesive was sprayed on Comparative Example 2.
[0089] Comparative Example 3: It is basically the same as Example 1, except that Comparative Example 3 does not have a reinforcing material wrapped around it.
[0090] Comparative Example 4: It is basically the same as Example 1, except that Comparative Example 4 uses foamed concrete without modified fibers.
[0091] Control group: The foamed concrete used in Comparative Example 5 did not contain modified fibers, and the amount of other raw materials was the same as in Example 1; no interface treatment was performed, and the foamed concrete was directly poured around the 3LPE steel pipe until the 3LPE steel pipe was completely covered and protected by the modified fiber-reinforced foamed concrete to obtain the specimen. Then, the specimen was cured under standard curing conditions of 20±5℃ and humidity ≥90%.
[0092] Performance testing: In the laboratory, the foamed concrete and 3LPE steel pipe composite structure specimens molded in Example 1 and Comparative Examples 1-4 were numbered T1 to T5 respectively; the control group specimen was numbered C1. In all specimens, the outer diameter of the 3LPE steel pipe was 108 mm, and its height was 300 mm; the foamed concrete coating layer had a height of 200 mm and a thickness of 100 mm. All specimens were removed after curing for 28 days for interfacial shear tests.
[0093] An interface shear test was performed on a microcomputer-controlled electro-hydraulic testing machine. A schematic diagram of the interface shear test is shown below. Figure 2As shown. Specifically, it includes the following steps: (1) Place the specimen 100 on the steel bearing support 202 at the bottom of the microcomputer-controlled electro-hydraulic testing machine. The lower end face of the foamed concrete layer of the specimen 100 contacts the surface of the steel bearing support 202. Adjust the position so that the axis of the specimen 100 is aligned with the center of the bearing platform 201 of the microcomputer-controlled electro-hydraulic testing machine.
[0094] (2) Start the microcomputer-controlled electro-hydraulic testing machine, adjust the upper bearing plate 203 to slowly move downwards until it fully contacts the top surface of one end of the 3LPE steel pipe 101 that is not wrapped with foamed concrete, and then begin loading. The test loading adopts displacement control, and the axial load (along the direction of the load) is controlled by the displacement. Figure 2 (In the direction of arrow 205), the axial loading speed of the testing machine is 5 mm / min, and the loading continues until the specimen 100 fails. The maximum axial force displayed by sensor 204 is recorded.
[0095] (3) Calculate the interfacial shear strength using the following formula: ; In the above formula: τ ax Represents axial shear strength (MPa); d represents the outer diameter of the steel pipe (mm). F ax Represents axial force (N); L represents the height (mm) of the modified fiber-reinforced foamed concrete layer.
[0096] The results of the performance tests are shown in Table 1.
[0097] As shown in Table 1, the experimental data reveals that the interfacial shear strength between foamed concrete and 3LPE steel pipe is only 0.20 MPa without any interface treatment or modification. However, the interfacial shear strength after treatment involving surface activation, interfacial chemical bonding, three-dimensional reinforcement anchoring, and material fiber modification reaches as high as 0.76 MPa, a 3.8-fold increase compared to the control group. This is because, without any treatment, the polarity difference between foamed concrete and 3LPE steel pipe results in low interfacial bonding, making them highly susceptible to shear failure under stress. The interface after treatment with surface activation, interfacial chemical bonding, three-dimensional reinforcement anchoring, and material fiber modification forms a triple reinforcement mechanism of "chemical bonding + mechanical interlocking + stress bridging," transforming the originally weak foamed concrete-pipe interface into a strong and tough composite interface layer. This not only improves the crack resistance and integrity of the foamed concrete itself but also significantly enhances the interfacial bonding strength and long-term durability between the foamed concrete and the oil and gas pipeline through stress transfer and energy dissipation in the composite interface layer.
[0098] The data comparison from T1 to T5 also shows that the application of interface adhesive and the wrapping of reinforcing material have the most significant impact on improving the interfacial shear strength. When no interface adhesive is applied, the interfacial shear strength is 56% lower than that of group T1 (i.e., Example 1); while when no reinforcing material is wrapped, the interfacial shear strength is 41% lower than that of group T1 (i.e., Example 1), further highlighting the interfacial reinforcement mechanism of the composite interface layer, which is dominated by "chemical bonding and mechanical anchoring, and surface activation and fiber bridging for auxiliary toughening".
[0099] Table 1
[0100] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.
Claims
1. A method for preparing an enhanced composite structure for the interface between foamed concrete and oil and gas pipelines, characterized in that, Includes the following steps: (1) Plasma activation treatment is performed on the outer surface of the 3LPE steel pipe to form a plasma activation interface layer; (2) A uniformly sprayed interface adhesive is applied to the surface of the plasma-activated interface layer to form an interface adhesive layer; (3) Wrap a reinforcing material around the surface of the interface adhesive layer; (4) Pour modified fiber-reinforced foamed concrete.
2. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 1, characterized in that, In step (1), the working gas is one or more of oxygen, nitrogen, and inert gas; the inert gas is helium or argon. The plasma radio frequency power is 150~400W, and the activation time is 20~90s.
3. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 2, characterized in that, In step (1), the working gas is a combination of oxygen and inert gas, and the volume ratio of oxygen to inert gas is 1:1 to 3:
1. The plasma activation treatment is performed using a radio frequency capacitively coupled plasma device or an inductively coupled plasma device.
4. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 1, characterized in that, The thickness of the interface adhesive layer is 0.2~0.5mm; The interface adhesive, by weight, is composed of the following raw materials: 80-100 parts of resin base material, 5-12 parts of reactive silane, 20-50 parts of aqueous alcohol solution, and 0.5-2 parts of thixotropic agent; The resin substrate is one or more of epoxy resin, polyurethane, phenolic resin, urea-formaldehyde resin, and polyacrylic acid resin. The reactive silane is one or more of aminosilane, epoxysilane, methacryloxysilane, vinylsilane, and isocyanate silane; The aqueous alcohol solution is composed of alcohol and water, wherein the mass ratio of water to alcohol is 9:1 to 7:3; and the alcohol is one of ethanol, methanol, or isopropanol. The thixotropic agent is fumed silica or organobentonite.
5. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 4, characterized in that, The method for preparing the interfacial adhesive includes the following steps: The aqueous alcohol solution is mixed with the resin substrate to obtain a resin solution; The reactive silane is added to the resin solution and hydrolyzed by stirring at 25~55°C; Add the thixotropic agent and stir until homogeneous to obtain the interfacial binder; During the stirring hydrolysis process, the stirring speed is 150~300 rpm, the stirring time is 5~10 min, and the hydrolysis time is 40~200 min.
6. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 1, characterized in that, In step (3), the reinforcing material is a three-dimensional mesh reinforcing material with a serrated surface. The reinforcing material is joined longitudinally and circumferentially using a binding and overlapping method.
7. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 6, characterized in that, The serrated height of the three-dimensional mesh reinforcement material with serrated features is 0.03 to 0.08 times the diameter of the steel pipe, the serration angle is 45° to 75°, and the ratio of the bottom spacing of the serrations to the serration height is (4 to 8):
1. The three-dimensional mesh reinforcement material with serrated features is galvanized steel wire mesh, steel-plastic geogrid, or alkali-resistant glass fiber mesh; The longitudinal and circumferential overlaps have an overlap length of 0.2~0.4D along the circumferential direction and an overlap length of 0.5~0.8D along the longitudinal direction.
8. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 1, characterized in that, In step (4), the modified fiber-reinforced foamed concrete covers the surface of the 3LPE steel pipe with a thickness of not less than 30cm. In step (4), the modified fiber-reinforced foamed concrete comprises, by weight, the following raw materials: 60-80 parts cement, 30-50 parts nano-reinforcing agent, 5-8 parts modified fiber, 0.5-3 parts foaming agent, and 50-80 parts first water; The cement is ordinary Portland cement with a strength grade of 425; The nano-reinforcing agent is one or more of nano-calcium carbonate, nano-silica, and nano-CSH particles. The foaming agent is one or more of the following: plant protein foaming agents, animal protein foaming agents, anionic foaming agents, cationic foaming agents, and amphoteric foaming agents. The modified fiber is obtained by grafting polar monomers onto the fiber surface for activation. The polar monomer is one or more of acrylic acid, methacrylic acid, acrylamide, glycidyl methacrylate, and maleic anhydride. The fiber is one or more of the following: polypropylene fiber, polyvinyl alcohol fiber, polyester fiber, glass fiber, and basalt fiber. The wet density of the modified fiber-reinforced foamed concrete is 800~1200 kg / m³. 3 .
9. The method for preparing the reinforced composite structure for the interface between foamed concrete and oil and gas pipelines according to claim 8, characterized in that, The method for preparing the modified fiber includes the following steps: The polar monomer was prepared into a modified solution with a concentration of 0.1–2.0 mol / L; The fiber is immersed in the modified solution and vacuum impregnated; The polar monomers are subjected to ultraviolet irradiation to cause free radical graft polymerization on the fiber surface; The modified fiber was obtained by washing with deionized water and vacuum drying to constant weight. The vacuum impregnation process is performed by vacuum impregnation at 25℃~40℃ for 2~4 hours; The ultraviolet irradiation process involves irradiating for 20 to 40 minutes under an ultraviolet lamp with a power of 500 to 1000W, at a distance of 10 to 20 cm. The vacuum drying process is carried out at 60~80℃; The preparation method of the modified fiber-reinforced foamed concrete includes the following steps: The cement, the nano-reinforcing agent, and the modified fiber are mixed evenly to obtain a first mixture; Add the first water to the first mixture and mix evenly to obtain the second mixture; The foaming agent is diluted with a second water at a dilution ratio of 50 to 80 times by mass, and then foamed to produce a product with a density of 30 to 50 kg / m³. 3 foam; The foam is added to the second mixture and mixed to obtain the modified fiber-reinforced foam concrete.
10. A reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, characterized in that, The reinforced composite structure for the interface between foamed concrete and oil and gas pipelines, as described in any one of claims 1-9, is prepared by the method for preparing such a structure, which includes: Steel pipe body; A 3LPE anti-corrosion coating is applied to the outer wall of the steel pipe body; The plasma-activated interface layer is the region formed on the outer surface of the 3LPE anti-corrosion coating by plasma activation treatment. An interface adhesive layer is disposed on the plasma-activated interface layer; The reinforcing material layer is longitudinally and circumferentially overlapped on the interface adhesive layer using a binding and overlapping method; A modified fiber-reinforced foamed concrete layer is disposed on the reinforcing material layer.
